2017
DOI: 10.1039/c7cp01462g
|View full text |Cite
|
Sign up to set email alerts
|

Band gap modulation of SrTiO3 upon CO2 adsorption

Abstract: CO 2 chemisorption on SrTiO 3 (001) surfaces is studied using ab initio calculations in order to establish new chemical sensing mechanisms. We find that CO 2 adsorption opens the material band gap, however, while the adsorption on the TiO 2 -terminated surface neutralizes surface states at the valence band (VB) maximum, CO 2 on the SrO-terminated surfaces suppresses the conduction band (CB) minimum. For the TiO 2 -terminated surface, the effect is explained by the passivation of dangling bonds, whereas for the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 83 publications
2
16
0
Order By: Relevance
“…Our calculations start with the interaction of the CO The formation of carbonate layer on SrTiO 3 surface was recently investigated with theoretical methods by Sopiha et al 25 In their study, they have shown that the carbonate layer significantly alters the electronic properties of the SrTiO 3 surface by increasing the surface band gap. The effect has been observed on both TiO 2 and SrO terminated surfaces.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our calculations start with the interaction of the CO The formation of carbonate layer on SrTiO 3 surface was recently investigated with theoretical methods by Sopiha et al 25 In their study, they have shown that the carbonate layer significantly alters the electronic properties of the SrTiO 3 surface by increasing the surface band gap. The effect has been observed on both TiO 2 and SrO terminated surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Amongst those phases the most important are the formation of surface carbonates, surface hydroxides, and physisorption or chemisorption of water molecules. [25][26][27] A knowledge of the real surface composition of ABO 3 perovskite air electrodes for solid oxide devices is crucial for the understanding of the chemical activity on the electrode surface and for the further optimization of electrode performance. Theoretical studies on surface termination of perovskites have so far been limited to the chemical composition of the investigated materials.…”
Section: Introductionmentioning
confidence: 99%
“…In order to avoid dipole-dipole interaction due to the cell periodicity, 58 CO2 chemisorption on both sides of the symmetrical slabs was modeled. This model was validated for SrTiO3(001) surfaces in our recent study 31 were computed as charge densities for the states within energy limits from the conduction band minima (CBM) or VBM levels of the slabs to those of the corresponding bulk compounds.…”
Section: Methodsmentioning
confidence: 99%
“…1a), in agreement with previous reports. 31,35, 64, 65 Although these energy gap reductions were observed for most investigated surfaces, the underlying mechanisms differ significantly among them. For the BO2-terminated ABO3(001), the effect is originated from the surface states emerging above the VBM of the bulk systems, as evident from the layer-resolved LDOS and projected surface state density shown in Fig.…”
mentioning
confidence: 93%
See 1 more Smart Citation